DD-012 Designing supply quotas of drugs in care units: how can we improve the methodology for double bin replenishment systems?. (24th March 2015) - Stuck, J; Gibert, P; Thorne, E; Brudieu, E; Foroni, L; Allenet, B
Abstract : Background: In our hospital, Double Bin Replenishment Systems (DBRS) are being progressively introduced into care units. For each DBRS, a supply quota of medicines is defined based on the unit's consumption during 6 months before the installation. Purpose: In September 2014, 43 care units were equipped by DBRS. Many qualitative and quantitative readjustments of the supply quotas are needed after installing them all. The purpose of this study was to analyse the supply quotas already established in order to critique our method of designing and to find a way to improve it. Material and methods: Qualitative analysis of drugs present in supply quotas in the care units where DBRS are already set up, according to the Anatomical Therapeutic Chemical classification (ATC) system. Results: There are 956 different drugs throughout the 43 supply quotas, which represent 45% of the drugs available in our hospital. None of them is found in every supply quota but 40 pharmaceutical specialties are present in more than 80% of care units and 139 in more than 50%. Qualitatively, all classes of the ATC classification system are represented in these 139 drugs, except for the antineoplastic and immunomodulating drugs and for the sensory organs' drugs, which are expensive drugs that are not commonly used in every medical ward. Based on these observations, we could improve the design of the supply quotas for the list of the 139 most represented pharmaceutical specialties. We propose developing a "standard supply quota" that could be used in all care units. These core supplies could then be added to by drugs specific to the unit. Conclusion: Supply quotas that are already implemented contain drugs of all ATC classes and may serve to define a "standard supply quota" that would be common to every care unit. References and/or acknowledgements: No conflict of interest.